Pengaruh Self Assessment System Dan Pemeriksaan Pajak Terhadap Penerimaan Pajak Pertambahan Nilai (PPN) Di KPP Pratama Surabaya Rungkut - Maria Yuliana Postel; J.B Amiranto (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study aims to determine and analyze and answer the role of self assessment system and tax audit on VAT revenue at KPP Pratama Rungkut Surabaya. This study uses a sampling technique, namely purposive sampling where the sample is taken with certain criteria, namely corporate taxpayers registered as taxable entrepreneurs who are still productive. This study takes secondary data in the form of documents obtained from KPP Pratama Rungkut including data on the number of VAT Periodic Tax Returns, VAT revenue realization data, data on the number of SKP values in 2020-2022. The type of research used is using quantitative research methods. The data analysis techniques used are multiple linear regression and . Meanwhile, the classical assumption tests used are normality, heteroscedasticity, autocorrelation and multicollinearity tests. Overall the indicators used are valid. The classical assumption results also meet, among others, the two regression models are free from multicollinearity, no heteroscedasticity, no autocorrelation, the residuals of the two regression models are normally distributed. The findings of this study indicate that the self-assessment system has a positive and significant effect on VAT revenue at KPP Pratama Rungkut Surabaya. Tax audit has no positive and significant effect on VAT revenue at KPP Pratama Rungkut. Self-assessment system and tax audit simultaneously have a positive and significant effect on VAT revenue at KPP Pratama Rungkut.